دور وسائل الإعلام في تشكيل الرأي العام (Comprehensive Journal of Science, 2025)
formation in light of the increasing reliance on technology and modern media, and compares its power and influence with traditional means such as family and school, with a focus on the role of media in shaping public opinion in ways that may not be compatible with existing systems.Research has shown that the information and communications revolution of the late 20th century was a key factor in shaping public opinion at all levels, leading to serious political, social, and global repercussions. This was achieved through the control and manipulation of media content, which helped shape public opinion and influence global decision-making. Public opinion is thus shaped by media outlets that serve the interests of their owners, who in turn exploit this power to craft messages that serve their objectives.
Keywords: Media, public opinion, shaping and influence, processes, tools and concepts.